Solar-driven zinc-doped graphitic carbon nitride photocatalytic fibre for simultaneous removal of hexavalent chromium and pharmaceuticals. Issue 17 (29th July 2022) - Zhu, Zhexin; Miao, Yongquan; Wang, Gangqiang; Chen, Wenxing; Lu, Wangyang
ABSTRACT: The current environmental problems urgently require researchers to seek an environmentally friendly, effective and easy to operate sewage treatment method. Graphite carbon nitride (g-C3 N4 ), which has the advantages of simple preparation, safety, non-toxicity and chemical resistance, was expected to become a photocatalyst for solving environmental pollution. However, the performances of g-C3 N4 still have some limitations that the electron hole recombination is fast and the powder is not easy to recover. In this study, zinc-doped graphite carbon nitride photocatalyst (Zn-g-C3 N4 ) was mixed with polyacrylonitrile (PAN) to produce photocatalyst fibres by electrospinning. It not only solves the problem that the powder catalyst is difficult to recycle, but also effectively inhibits the recombination of photoelectron-hole pairs. Zn-g-C3 N4 /PAN has good photocatalytic activity for the simultaneous reduction of hexavalent chromium and degradation of pharmaceuticals. When organic pollutants are present, the reduction efficiency of hexavalent chromium was improved without affecting its own removal efficiency. The potential application value of Zn-g-C3 N4 /PAN catalytic fibre was further explored by simulating the complex actual water environment. The composite fibre can be easily reused and keep its superior photocatalytic performance. The mechanism of pharmaceuticals degradation was proposed, in which ∙ O 2 − is the most important active species, which leads to the oxidation of pharmaceuticals. Besides, the photoelectrons generated by the catalyst can reduce the toxic hexavalent chromium. The efficiency of Zn-g-C3 N4 to remove pollutants is improved by PAN fibre as a carrier, which not only solves the problem of difficult recovery of powder catalysts, but also provides more active sites. GRAPHICAL ABSTRACT: UF0001